2000
DOI: 10.1080/016128400750044279
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and Depression in Caregivers of Persons With Alzheimer's Disease or Related Disorders

Abstract: Secondary analysis of data from a sample of 242 husbands, wives, and daughters providing care for Alzheimer's disease family members was conducted to examine the relationships among loneliness and depression and the following variables: quality of the past relationship, relational deprivation, quality of the current relationship, and distance felt due to caregiving. Loneliness was significantly related to depression (r = .66, p < .001), relational deprivation (r = .36, p < .001), and quality of the current rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 49 publications
5
102
1
2
Order By: Relevance
“…The role of gender in the expression and experience of aggression has largely been overlooked, with most studies of the causal factors of elder abuse focusing on characteristics such as caregiver stress or substance abuse (Neysmith 1995, Whittaker 1995. Mother-daughter relationships are lifelong enduring relationships that seldom end (Fingerman 2001) and the dynamics of mother-daughter dyads are different from those of other family member dyads (Beeson et al 2000, King et al 2002, Rozario et al 2008. Therefore, a gendered examination of the dynamics of this unique relationship is warranted.…”
Section: Introductionmentioning
confidence: 96%
“…The role of gender in the expression and experience of aggression has largely been overlooked, with most studies of the causal factors of elder abuse focusing on characteristics such as caregiver stress or substance abuse (Neysmith 1995, Whittaker 1995. Mother-daughter relationships are lifelong enduring relationships that seldom end (Fingerman 2001) and the dynamics of mother-daughter dyads are different from those of other family member dyads (Beeson et al 2000, King et al 2002, Rozario et al 2008. Therefore, a gendered examination of the dynamics of this unique relationship is warranted.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, social isolation is associated with depression [29]. From this perspective, it seems logical to assume that being anxious and feeling alone are part of the same topic.…”
Section: Comprehensive Understanding and Discussionmentioning
confidence: 99%
“…The levels of loneliness in mothers of children patients with cancer, in relatives of patients with Parkinson's disease, and in relatives of patients with Alzheimer's disease were reported as 41.41±11.75, 40±10.6, and 37.35±9.7 respectively (Beeson et al, 2000;Bal Yılmaz et al, 2008;McRae et al, 2009). These findings are in line with our study findings.…”
Section: Discussionmentioning
confidence: 99%
“…And, although there was no statistically significant difference between mean loneliness scores of caregivers and degree of relationship between the caregiver and patient, the mean loneliness score was found to be higher in caregiver spouses (Table 5). Beeson et al (2000) reported that the degree of relatives was effective on loneliness. Kılıç Akça and Taşçı (2005) stated that the mental health problems experienced by caregivers of patients over 65 years old increase with decreasing degree of relatedness.…”
Section: Discussionmentioning
confidence: 99%